1996
DOI: 10.1161/01.str.27.12.2191
|View full text |Cite
|
Sign up to set email alerts
|

Can Motor Recovery in Stroke Patients Be Predicted by Early Transcranial Magnetic Stimulation?

Abstract: We conclude that early-performed transcranial magnetic stimulation is a valuable prognostic tool for motor recovery from stroke and that relatively preserved MEP amplitude shortly after stroke is a better prognostic factor than normal central motor conduction time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 11 publications
4
62
0
Order By: Relevance
“…In a number of Most TMS studies have shown that presence of contralaclinical trials, there have been behavioral improvement teral MEPs early after the stroke is a marker for good even in patients with chronic and apparently stable stroke. recovery [2,8,9,20,31,46,53,55,62]. Preservation of corLiepert and co-workers [38,39] have shown that TMS ticospinal tract with MRI imaging was also found to maps increase in size in this circumstance showing that the correlate with good recovery confirming the TMS studies expected cortical changes appear to be occurring.…”
Section: Mechanisms Of Plasticitymentioning
confidence: 83%
“…In a number of Most TMS studies have shown that presence of contralaclinical trials, there have been behavioral improvement teral MEPs early after the stroke is a marker for good even in patients with chronic and apparently stable stroke. recovery [2,8,9,20,31,46,53,55,62]. Preservation of corLiepert and co-workers [38,39] have shown that TMS ticospinal tract with MRI imaging was also found to maps increase in size in this circumstance showing that the correlate with good recovery confirming the TMS studies expected cortical changes appear to be occurring.…”
Section: Mechanisms Of Plasticitymentioning
confidence: 83%
“…Our data contribute to this issue, by suggesting that a combination of two relatively easily obtainable parameters could support decisions concerning the rehabilitation process. Some studies conducted in the acute phase of stroke showed, using MEP threshold and amplitude measures, a relationship between motor recovery and the degree of motor impairment (Pennisi et al, 1999;Pizzi et al, 2009;Rapisarda et al, 1996). The absence of MEPs, more than amplitude variations, seems to be predictive of recovery (Di Lazzaro et al, 2010), but consensus on this issue is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that the TMS technique in particular evaluates the corticospinal motor pathway, and thus motor function, 18 while the Barthel Index depends on other factors in addition to strength. 20 The utilization by some authors 30,33 of MEP amplitude as the most sensitive parameter involves the problem of its important variability. 26,34 In this sense, we are of the opinion that MEP amplitude is of use when applied in combination with changes in latency and threshold (which usually occur together), while its isolated application does not contribute more information.…”
Section: Escudero Et Al September 1998mentioning
confidence: 99%